2017
DOI: 10.1155/2017/5871756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Heat and Preservative Treatment on Storability of Ponkan Fruit (Citrus reticulataBlanco cv. Ponkan) during Postharvest Storage

Abstract: Heat treatment and preservative application have been widely used during postharvest storage of many fresh products, but the effect of their combination on citrus storage has rarely been investigated. In this study, the optimal heat treatment (HT) conditions and HT combined with preservative treatment were investigated for Ponkan fruit (Citrus reticulata Blanco cv. Ponkan) storage. Results indicated that HT at 55 ∘ C for 20 s can significantly reduce the decay rate of Ponkan fruit, and a combination of HT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Its fruit matures in mid-November to late December. The skin of mature Ponkan is orange and easy to peel, and the pulp is crisp and juicy, with a strong flavor [2]. In actual production, based on cost and technical constraints, the fruit growers usually store the picked Ponkan fruits at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Its fruit matures in mid-November to late December. The skin of mature Ponkan is orange and easy to peel, and the pulp is crisp and juicy, with a strong flavor [2]. In actual production, based on cost and technical constraints, the fruit growers usually store the picked Ponkan fruits at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Ponkan mandarins (Citrus reticulata Blanco, PM) are one of the main loose-skin citrus cultivars and are widely cultivated in Southern China. Jing'an Ponkan mandarin is a famous mandarin variety in Jiangxi Province, characterised by a compact plant type, early fruit bearing, rounded fruit shape, bright colour, sweet taste, crisp flesh, high storability, and late maturity (Tang et al, 2017;Gao et al, 2018). These mandarins are a major source of economic income for fruit growers in the Jing'an area.…”
Section: Introductionmentioning
confidence: 99%
“…Cold storage is the most frequently used preservation technology to maintain postharvest quality and extend the storage life of fresh citrus fruits, such as grapefruits, mandarins, tangerines and lemons (Montero et al, 2009;Undurraga et al, 2009;Chaudhary et al, 2017;Matsumoto et al, 2019). The recommended storage temperatures (RST) for postharvest citrus fruit range from 5 °C to 8 °C (Tietel et al, 2012). However, Ponkan mandarins are highly susceptible to the damage of chilling injury (CI) in the peel when stored at the RST condition (Zhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Citrus fruit is citric acid type fruit Main text paragraph [ 1 ]. Ponkan ( Citrus reticulata Blanco) is one of the main mandarin citrus in China, the fruit are rich of organic acid [ 2 ]. Zhang et al [ 3 ] have demonstrated that citric acid was the major organic acid in Ponkan fruit, which accountings for 91.82% of the total content in single fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Hot air treatment as a common method has been used for many species of fruit and vegetable after harvest, such as strawberry [ 8 ], peaches [ 9 ], 'Qingnai' plum [ 10 ] and citrus fruit [ 2 , 11 ]. Heat treatment of 50°C for 5–10 minutes could delay the change of storage quality of sweet orange fruit and reduce the occurrence of fruit decay [ 12 ].…”
Section: Introductionmentioning
confidence: 99%